Konsep Pendidikan Karakter Berbasis Cinta Perspektif Al-Qur’an dan Hadis - Makmudi Makmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Philosophical foundation of education. This has implications for an excessive euphoria of freedom. Education in Islam is not solely oriented toward mastery of knowledge, but also toward the development of students' character and spirituality. One of the main foundations of Islamic education is love (mahabbah), which serves as the foundation for the relationship between educators and students, and between humans and Allah SWT. The purpose of this study is to examine and analyze the concept of love-based character education from the perspective of the Quran and Hadith. This research method utilizes library research with a thematic interpretation approach. This study found that love-based education emphasizes compassion, gentleness, exemplary behavior, and spiritual motivation in the learning process. This principle aligns with the prophetic mission of the Prophet Muhammad (peace be upon him) as rahmatan lil 'alamin. Thus, love-based character education can be an alternative paradigm for building a humanistic, transformative, and noble education system.